Regulator of Lipid Metabolism NHR-49 Mediates Pathogen Avoidance through Precise Control of Neuronal Activity - Saebom Kwon; Kyu-Sang Park; Kyoung-hye Yoon (Cells, 2024)
Precise control of neuronal activity is crucial for the proper functioning of neurons. How lipid homeostasis contributes to neuronal activity and how much of it is regulated by cells autonomously is unclear. In this study, we discovered that absence of the lipid regulator nhr-49, a functional ortholog of the peroxisome proliferator-activated receptor (PPAR) in Caenorhabditis elegans, resulted in defective pathogen avoidance behavior against Pseudomonas aeruginosa (PA14). Functional NHR-49 was required in the neurons, and more specifically, in a set of oxygen-sensing body cavity neurons, URX, AQR, and PQR. We found that lowering the neuronal activity of the body cavity neurons improved avoidance in nhr-49 mutants. Calcium imaging in URX neurons showed that nhr-49 mutants displayed longer-lasting calcium transients in response to an O2 upshift, suggesting that excess neuronal activity leads to avoidance defects. Cell-specific rescue of NHR-49 in the body cavity neurons was sufficient to improve pathogen avoidance, as well as URX neuron calcium kinetics. Supplementation with oleic acid also improved avoidance behavior and URX calcium kinetics, suggesting that the defective calcium response in the neuron is due to lipid dysfunction. These findings highlight the role of cell-autonomous lipid regulation in neuronal physiology and immune behavior.